2016
DOI: 10.1007/s10120-016-0620-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic ability of magnifying endoscopy with blue laser imaging for early gastric cancer: a prospective study

Abstract: Background Blue laser imaging (BLI) is a new image-enhanced endoscopy technique that utilizes a laser light source developed for narrow-band light observation. The aim of this study was to evaluate the usefulness of BLI for the diagnosis of early gastric cancer. Methods This single center prospective study analyzed 530 patients. The patients were examined with both conventional endoscopy with white-light imaging (C-WLI) and magnifying endoscopy with BLI (M-BLI) at Kyoto Prefectural University of Medicine betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 23 publications
2
63
0
1
Order By: Relevance
“…Magnifying BLI (M-BLI) is useful for evaluating mucosal microvessels and mucosal microstructures of EGC [17,18]. Furthermore, M-BLI is more accurate than C-WLI for diagnosing EGC according to the vessel plus surface (VS) classification system [19]. However, to date, no study has compared M-BLI and M-NBI in terms of endoscopic findings of EGC.…”
Section: Introductionmentioning
confidence: 99%
“…Magnifying BLI (M-BLI) is useful for evaluating mucosal microvessels and mucosal microstructures of EGC [17,18]. Furthermore, M-BLI is more accurate than C-WLI for diagnosing EGC according to the vessel plus surface (VS) classification system [19]. However, to date, no study has compared M-BLI and M-NBI in terms of endoscopic findings of EGC.…”
Section: Introductionmentioning
confidence: 99%
“…This emphasizes the importance of image-based diagnoses in achieving an accurate diagnosis of EGC. A series of studies demonstrated that the combined use of magnifying endoscopy and IEEs was useful in discriminating cancerous from noncancerous mucosa [15][16][17][18][19]. Most of these studies investigated NBI-assisted diagnoses.…”
Section: Differential Diagnosis and Delineation With Ieementioning
confidence: 99%
“…The combination of strong 410 nm laser light, weak 450 nm laser light, and fluorescent light enables blue laser imaging (BLI) via narrow-band light observation. Magnifying endoscopy with BLI is useful for evaluating mucosal surface information such as surface blood vessel and structure patterns (11)(12)(13)(14)(15). The present study reported that the diagnostic ability of magnifying BLI endoscopy in early gastric cancer is higher than that of conventional white light endoscopy and was similar to that of magnifying NBI endoscopy (15 Magnifying BLI is also potentially useful in distinguishing Hp-positive stomachs as magnifying NBI.…”
Section: Introductionmentioning
confidence: 58%
“…The system provides a high contrast clear view of fine mucosal and capillary structures. Diagnostic effectiveness of BLI endoscopy has been suggested in colorectal tumors and early gastric cancers (11,15). The current study presents new evidence that magnifying BLI endoscopy is useful in distinguishing Hp-positive stomach.…”
Section: Discussionmentioning
confidence: 74%